2016
DOI: 10.4324/9781315686660
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and Leisure Mobilities

Abstract: This book reframes tourism, as well as leisure, within mobilities studies to challenge the limitations that dichotomous understandings of home/away, work/ leisure, and host/guest bring. A mobilities approach to tourism and leisure encourages us to think beyond the mobilities of tourists to ways in which tourism and leisure experiences bring other mobilities into sync, or disorder, and as a result re-conceptualises social theory. The anthology stretches across academic disciplines and fields of study to illustr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 163 publications
(210 reference statements)
0
1
0
Order By: Relevance
“…Structural changes and complex destination management together with changing nature of community itself induced by mobilities have challenged the traditional, fixed and closed communities and made them more fluid in both space and time. Rickly et al (2016) conclude that the present community could be identified as a group of people sharing common values, beliefs and identities yet not essentially dwell in the same geographical area. This was observed factual in the context of fast moving tourist destinations observed in this study.…”
Section: Discussionmentioning
confidence: 88%
“…Structural changes and complex destination management together with changing nature of community itself induced by mobilities have challenged the traditional, fixed and closed communities and made them more fluid in both space and time. Rickly et al (2016) conclude that the present community could be identified as a group of people sharing common values, beliefs and identities yet not essentially dwell in the same geographical area. This was observed factual in the context of fast moving tourist destinations observed in this study.…”
Section: Discussionmentioning
confidence: 88%